Persepsi Masyarakat Terhadap Produk Sirup Buah Pala “Pore” di Kecamatan Luwuk - Ratmi Rosilawati; Dwi Wijayanti; Lutfi Samaduri; Restu Alfriandi (Universitas Muhammadiyah Luwuk, 2023)
Abstract: Processing of nutmeg-based syrup products is still very rare. Processing of nutmeg syrup is a good breakthrough in the diversification of foodstuffs. The purpose of this study was to examine public perceptions through organoleptic tests of Nutmeg Syrup owned by a business from the Faculty of Agriculture in Luwuk District, Banggai Regency. To determine public acceptance from the aspects of taste, texture, aroma, color, price and packaging. The research was conducted in Luwuk District, Banggai Regency in July - August 2022. The research area was determined based on the criteria that the sub-district contained businesses owned by the Faculty of Agriculture. Random sampling data collection method, by conducting direct interviews with respondents, namely as many as 60 respondents who were divided based on age from 15 years to 25 years totaling 30 people and from 26 to 50 years old totaling 30 people. The results of the study were respondents' perceptions of the introduction of nutmeg syrup products in Luwuk sub-district, Banggai Regency, out of a total of 60 respondents, all with a percentage of 100% stated that they had never heard of and consumed nutmeg syrup before and respondents' perceptions of pore nutmeg syrup products were tested using 6 indicators, namely texture , color, taste, aroma, price and packaging have positive feedback or received. Keywords: Nutmeg Syrup,Organoleptic, Public Perception